Penghimpunan Dana Akad Mudharabah dalam Perbankan Syariah - Seri Mughni Sulubara (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Fund raising is the business activity of financial institutions in attracting and collecting funds. Mudharabah or can be called al-mudharabah is a business cooperation contract between two parties in which the first party (shahibul maal) to provide all (100%) capital, while the other party becomes the manager. With an optimal profit sharing scheme, it is hoped that a fair distribution of profit sharing between the bank (shahibul mall) and the customer (mudharib) can be realized so as to minimize the risk of agency problems in mudharabah financing. The research objective is to find out the Mudharabah Fund Raising in Islamic Banking. The research method is to use qualitative methods. That the collection of mudharabah contract funds in Islamic banking is carried out through savings products and current account products.